Nuclear transmembrane protein 199 promotes immune escapes by up-regulating programmed death ligand 1 - Wulin You; Hue Luu; Meili Li; Zhiyu Chen; Fangchao Li; Yanfei Zhang; Mingsheng Cai; Tong-chuan He; Jingjing Li (iScience, 2024)
Summary: The function of transmembrane protein 199 (TMEM199) in cancer development has rarely been studied thus far. We report the nuclear localization of the TMEM199 protein and further analyzed the truncated fractions that mediate its nuclear localization. Cut&Tag assay globally explores the nuclear-located TMEM199 functions and tests its influence on the immune checkpoint PD-L1 in vitro and in vivo. Nuclear-located TMEM199 regulates PD-L1 mRNA levels by binding to transcription factors such as IFNGR1, IRF1, MTMR9, and Trim28, which all promote PD-L1 mRNA expression. Our study demonstrates the nuclear localization of TMEM199 and its immune regulation functions in cancer development. We uncovered the nuclear localization of TMEM199. TMEM199 is involved in CD274 mRNA gene expression by the transcriptional regulation of the upstream transcription factors or cofactors of CD274, such as IFNGR1, IRF1, MTMR9, KAT8, and Trim28. The nuclear-located TMEM199 is reported to address the tumor immune microenvironment commanding function.